Powerful fermentative hydrogen evolution of photosynthate in the cyanobacterium Lyngbya aestuarii BL J mediated by a bidirectional hydrogenase - Kothari, Ankita; Parameswaran, Prathap; Garcia-Pichel, Ferran (Frontiers in Microbiology, 2014)
Cyanobacteria are considered good models for biohydrogen production because they are relatively simple organisms with a demonstrable ability to generate H2 under certain physiological conditions. However, most produce only little H2, revert readily to H2 consumption, and suffer from hydrogenase sensitivity to O2. Strains of the cyanobacteria Lyngbya aestuarii and Microcoleus chthonoplastes obtained from marine intertidal cyanobacterial mats were recently found to display much better H2 production potential. Because of their ecological origin in environments that become quickly anoxic in the dark, we hypothesized that this differential ability may have evolved to serve a role in the fermentation of the photosynthate. Here we show that, when forced to ferment internal substrate, these cyanobacteria display desirable characteristics of physiological H2 production. Among them, the strain L. aestuarii BL J had the fastest specific rates and attained the highest H2 concentrations during fermentation of photosynthate, which proceeded via a mixed-acid fermentation pathway to yield acetate, ethanol, lactate, H2, CO2 and pyruvate. Contrary to expectations, the H2 yield per mole of glucose was only average compared to that of other cyanobacteria. Thermodynamic analyses point to the use of electron donors more electronegative than NAD(P)H in Lyngbya hydrogenases as the basis for its strong H2 production ability. In any event, the high specific rates and H2 concentrations coupled with the lack of reversibility of the enzyme, at the expense of internal, photosynthetically generated reductants, makes L. aestuarii BL J and/or its enzymes, a potentially feasible platform for large-scale H2 production.